Some Further Results on Consistency, Rationality and Collective Choice - Richelson, Jeffrey (Review of Economic Studies, 1978)
Journal Article Some Further Results on Consistency, Rationality and Collective Choice Get access Jeffrey Richelson Jeffrey Richelson Analytical Assessments Corporation Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 343–346, https://doi.org/10.2307/2297348 Published: 01 June 1978 Article history Received: 01 September 1976 Accepted: 01 April 1977 Published: 01 June 1978